Beryllium concentrations and ratios (10Be/9Be) of sediment cores PS67/197-1, PS75/054-1, and PS97/085-3 - Loftfield, Julia; Nowaczyk, Norbert R; Lembke-Jene, Lester; Frederichs, Thomas; Lachner, Johannes; Lamy, Frank; Rugel, Georg; Stübner, Konstanze; Adolphi, Florian
We obtained high resolution records of authigenic 10Be/9Be ratios in order to study the different impacts on 10Be deposition in marine sediments compared to ice cores. As changes in the atmospheric production of cosmogenic 10Be leave a global fingerprint in 10Be deposition fluxes this represents a powerful tool for the synchronization of climate archives. During the Laschamps geomagnetic field low (~ 41 ka BP) the global production rate of 10Be is expected to double. We therefore chose the depth intervals covering this period (PS67/197-1 8.51 – 16.31 m; PS75/054-1 1.80 – 8.30 m; PS97/085-3 3.80 – 7.60 m). For Be measurements 0.5 – 3.0 g of freeze dried samples of the cores were leached (Gutjahr et al., 2007), purified (Loftfield et al., 2024), and measured via ICP-OES (9Be) and AMS (10Be; Lachner et al., 2023 and Rugel et al., 2016). High resolution paleo- and mineralmagnetic measurements were performed on the 2.37 m – 15.36 m (~ 27 – 82 ka BP) interval of PS75/054-1 in order to improve the age model of that core. The magnetic susceptibility and paleomagnetic measurements of PS67/197-1 and PS97/085-3 have been described and published by Xiao et al. (2016) and Wu et al. (2021), respectively. For age model construction the time scales of EDC and EDML were updated to AICC2023.